Morphometric Analysis of Local Fish from Banyu Biru Lake, Pasuruan Compared with Closely Related to Tor spp. from Indonesia - Rahayu, Dwi Anggorowati; Nugroho, Endik Deni; Azrianingzih, Rodliyati; Kurniawan, Nia; Haryono, Haryono (Journal of Tropical Life Science, 2013)
Banyu Biru is a natural lake in Sumber Rejo Village, Winongan District, Pasuruan Regency. There are local fishes in the Banyu Biru called sengkaring and tambra. Biological studies on these fishes are not so much known. This study aims to identify the relationship of sengkaring and tambra compared with the related species ( Tor spp.: Cyprinidae) from Indonesia. Morphometric analysis can be used to clustering and understanding the relationship of taxa. Each species represents 17 specimens (Tambra and Sengkaring) and measured 22 characters (in mm) by using digital caliper and the additional characters (21 characters). The canonical, clustering, similarity and distances were used. Based on morphometric measurements, sengkaring and tambra had similarity with the four species found in Indonesia. Commonly, the population of Sengkaring and Tambra was critical; therefore, studies needed to be carried out to support conservation.